Sosialisasi Akuntansi dan Perpajakan Bagi UMKM di Kelurahan Rancamaya, Bogor - Luh Nadi; Harry Barli; Thom Deutmar Londo Doaly (Abdimisi, 2022)
We have carried out PKM odd semester 2022/2023 in Rancamaya Village, South Bogor District, Bogor. The theme of this PKM activity is "Accounting and Taxation Socialization for MSMEs in Rancamaya Village, Bogor". The main focus of this PKM activity is to provide socialization to MSMEs in the Rancamaya Village regarding Basic Accounting and Taxation. This is due to a lack of understanding of accounting, especially regarding recording and bookkeeping and a lack of understanding of taxation, so MSME actors rarely calculate income and report taxes that need to be paid. This discussion of accounting and taxes is expected to provide knowledge on how to calculate or record and record income earned and can also provide knowledge on how to calculate taxes in accordance with tax rules. The method used in this service provides counselling and tax calculations. The result of this PKM is that participants become increasingly aware of the need for bookkeeping and compliance with applicable tax regulations.